IMPOLITENESS OF COLLEGE STUDENT SHORT MESSAGE SERVICE TOWARD THE LECTURER (KETIDAKSANTUNAN DALAM PESAN SINGKAT MAHASISWA KEPADA DOSEN) - Fhitri, S.S, M.Hum, Widya; Yalmiadi, Yalmiadi (Universitas PGRI Sumatera Barat, 2018)
This study aims to describe and explain the strategy of dishonesty, politeness indicator, and factors used in short messages students to the lecturerin Dharma Andalas univeristy. This research uses qualitative descriptive analysis. The data of this research is the utterance that happened between student and lecturer. In collectingdata, this research used reference method. This method is followed by the technique of record. Data is done by recording a short message that goes to the lecturer's mobile phone. The method of data analysis used in this study is a method of technicalwith pragmatic, referential, and translational. The method of presentation of thisresearch results isused formal and informal methods. The results of the data analysis showed that the strategy of impoliteness that commonly used by the students is bald on record impolitenes, followed by positive impoliteness and negative impoliteness. While the indicator of politeness is often used is to use the word sorry, please and should. Another factor that causes the most frequent of impoliteness is direct criticism with hard words.